The Figure of the Mother in the Cases of the Latin American Presidents Michelle Bachelet (Chile), Cristina Fernández (Argentina) and Dilma Rousseff (Brazil) [a Figura Da Mãe Nos Casos Das Presidentas Latino-Americanas Michelle Bachelet (Chile), Cristina Fernández (Argentina) y Dilma Rousseff (Brasil)] [la Figura de la Madre en Los Casos de Las Presidentas Latinoamericanas Michelle Bachelet (Chile), Cristina Fernández (Argentina) y Dilma Rousseff (Brasil)] - Valenzuela-Somogyi, M (Universidad de los Andes, Bogota Colombia, 2019)
Women’s political action in Latin America has been predominantly represented by the figure of the mother. However, comparative research that focuses on contemporary feminine political leaderships is scarce. Using a qualitative content analysis of speeches and interviews of three Latin American presidents during their terms —Cristina Fernandez (Argentina), Dilma Rousseff (Brazil) and Michelle Bachelet (Chile)—, we propose three key figures, related to the maternal image, that are used to think about the manners in which each president is positioned within contemporary strategic frameworks: 1) the instrumental mother, 2) the “super-mother” and 3) the contemporary mother. © 2019, Universidad de los Andes, Bogota Colombia. All rights reserved.